If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + -2x = 4(2 + -3x) + 8x 6 + -2x = (2 * 4 + -3x * 4) + 8x 6 + -2x = (8 + -12x) + 8x Combine like terms: -12x + 8x = -4x 6 + -2x = 8 + -4x Solving 6 + -2x = 8 + -4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4x' to each side of the equation. 6 + -2x + 4x = 8 + -4x + 4x Combine like terms: -2x + 4x = 2x 6 + 2x = 8 + -4x + 4x Combine like terms: -4x + 4x = 0 6 + 2x = 8 + 0 6 + 2x = 8 Add '-6' to each side of the equation. 6 + -6 + 2x = 8 + -6 Combine like terms: 6 + -6 = 0 0 + 2x = 8 + -6 2x = 8 + -6 Combine like terms: 8 + -6 = 2 2x = 2 Divide each side by '2'. x = 1 Simplifying x = 1
| 9=-2m+-1 | | .93x+.97(4-x)=3.8 | | 2(x-4)-x=3 | | (3x-3)(3x-8)= | | 1+8(-4n-2)=-39-8n | | -2/3r+2r=6/5r+12/5 | | (4x^2+1)(6x^2+7)= | | 5x-6-2x=4x+8 | | 6x+6=6x-9 | | 2/3(6x+9)=18 | | -8v=-80 | | -2(-x-8)=2x+15 | | -3(x-5)+12x=9(x+2)+12 | | 60+15=4 | | d-16=-50 | | 2(6w+8)=2(4w+24) | | (3x+5)=2(x+7) | | -6(x-8)=48 | | n+t+g+h=106 | | 162=11x+19 | | 3(x+5)+4x=-(x-5) | | x-1=-4*1 | | 34+4k=102 | | 15=3xy-1 | | 0.75n-3=-9 | | 2/3+4=8 | | 64=4v | | M=1/k+n | | W=x-y/2 | | 3x-8x-4=8x | | j/6-9=5/9 | | x-27=43 |